Compressive behaviour and design of CFDST cross-sections with stainless steel outer tubes - Wang, Fangying (2021)
A finite element (FE) investigation into the compressive behaviour of concrete-filled double skin tubular (CFDST) cross-sections with lean duplex and ferritic stainless steel outer tubes is presented. FE models were initially developed and validated against available test results reported in the literature. Upon successful replication of the ultimate capacities, load–deformation histories and failure modes exhibited by the tested CFDST stub columns, a parametric study was undertaken to investigate the influence of key variables, including the local slendernesses of the outer and inner tubes, the concrete strength and the adopted grade of stainless steel, on the ultimate response of the studied CFDST stub columns. Based on the generated FE data pool and the available test results, the applicability of the existing European, Australian and American design provisions for composite carbon steel members to the design of the studied CFDST cross-sections was evaluated. All the examined design rules are shown to yield unduly conservative (less so for the higher concrete grades) and rather scattered capacity predictions. Modifications to the design treatment in relation to the effective area of the outer tubes, to take due account of outward-only local buckling, and the effective compressive strength of the infilled concrete, to reflect the reduced relative effectiveness of higher concrete grades, are considered. The modified design rules are shown to improve the accuracy and consistency of the design capacity predictions. Finally, statistical analyses were carried out to demonstrate the reliability of the modified design approaches.